World society and globalisation. Issue 3 (5th August 2014) - Gilbert Ahamer, Professor Glenn Hardaker, Dr; Wittmann, Veronika
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to illustrate discourses on globalisation and world society and to disclose the commonalities and differences of both scientific debates. In particular, it draws attention to theoretical concepts of globalisation and world society. This is considered fruitful for comprehending the complex mechanisms of sociological theory-building in a globalised world. Design/methodology/approach – The article first contextualises the multi-dimensionality and ambiguity of globalisation. It then reflects on the consequences of globalisation for socio-scientific considerations. The third part of the paper highlights scientific discourses on world society and globalisation, especially illustrating the commonalities and differences of both debates. In the concluding remarks of the article, discourses on world society are presented as a seismograph of contemporary socio-scientific debates encountering processes of globalisation. Findings – The paper does not simply present scientific discourses as isolated from a globalised world, but discloses the challenges of socio-scientific disciplines facing the global frame of reference for research. To balance the research analyses of scientific discourses, those on globalisation and world society are illustrated. Originality/value – The interplay between discourses on globalisation and those on world society is rarely reflected upon in publications. This paper provides insights into how, on the one hand, scientific debates on globalisation and on world society act together as part and parcel of the overall global frame of reference for research, yet it also shows, on the other hand, how different the discourses are. Furthermore, it highlights the prospective role of socio-scientific disciplines in a globalised world.